A suboptimal approach to channel equalization based on the nearest neighbor rule. - Savazzi, P.
Applications of clustering and neural network techniques to channel equalization have revealed the classification nature of this problem. This paper illustrates an implementation of a global system for mobile communications (GSM) receiver in which channel equalization and demodulation are realized by means of the nearest neighbor (NN) classifier algorithm. The most important advantage in using such techniques is the significant reduction in terms of the computational complexity compared with the maximum likelihood sequence estimation (MLSE) equalizer. The proposed approach involves symbol-by-symbol interpretation and the knowledge of the channel is embedded in the mapping process of the received symbols over the symbols of the training sequence. This means that no explicit channel estimation need be carried out, either with correlative blocks or using neural networks thus speeding up the entire process. The performance of the proposed receiver, evaluated through a channel simulator for mobile radio communications, is compared with the results obtained by means of a 16-state Viterbi algorithm and other suboptimal receivers. It is shown that the presented algorithm increases the bit error rate (BER) compared with the MLSE demodulator, but the performance degradation, despite the simplicity of the receiver, is kept within the limits imposed by the GSM specifications
Keywords: 16-state Viterbi algorithm; BER; GSM receiver; GSM specifications; MLSE demodulator; MLSE equalizer; Bit error rate; Channel equalization; Channel simulator; Clustering techniques; Computational complexity reduction; Demodulation; Global system for mobile communications; Mapping process; Maximum likelihood sequence estimation; Mobile radio communications; Nearest neighbor classifier algorithm; Nearest neighbor rule; Neural network techniques; Pattern classification; Performance; Suboptimal approach; Suboptimal receivers; Training sequence